Dynamics of a mass variable drum winding a heavy rope - Buśkiewicz, J. (Archives of Mechanics, 2021)
The paper focuses on a winch drum winding a heavy rope to present the variety of issues related to the dynamics of systems with rotating parts of time-varying mass. The dynamic motion equations for such systems are frequently either incorrect or derived under the assumption of mass constancy. When the mass variability is taken into account, simpler cases are discussed. The considerations on the angular momentum theorem enables formulating a new two time parameters form of the rotational motion equation for the system with time varying mass. Four cases are considered and different approaches of motion equations derivation are applied. The assumptions and solution methods of the analyzed systems as well as ambiguities and possible contradictions that may arise as a result of the trial of the problem formulation on the grounds of rigid body mechanics are discussed. The numerical simulations are presented.